Processos facilitadores e barreiras de acesso do pré-natal odontológico em um município de pequeno porte de Minas Gerais - Maria Eleonora Queiroz dos Santos (2023)
Prenatal dental care (PNO) is important for promoting the oral health of pregnant women and preventing the spread of oral diseases during pregnancy, as well as the adoption of healthy behaviors for the oral health care of mother and baby. The aim of this study was to identify the factors responsible for the low proportion of pregnant women attending the PNO in this municipality and to propose the implementation of a protocol to change this situation. A quantitative and qualitative study was carried out using a questionnaire and focus groups with health professionals involved in the PNO at three Basic Health Units (BHU). A pilot study was carried out with a similar population to calibrate the researcher and adjust the questionnaire and script. The health professionals were invited and those who agreed to take part signed an informed consent form. At this point, they filled in the Interprofessional Collaboration readiness assessment scale with demographic and work-related data. Afterwards, a focus group was held with a script that addressed questions about the perception of the importance of and factors that interfere with PNO, teamwork and the flow of care. The quantitative data was entered into the Excel program and analyzed using the SPSS software with descriptive statistical analysis. The qualitative data was analyzed using thematic content analysis. Ethical precepts were respected (CAAE: 64538622.7.0000.5149). In 2021, when the study was proposed, the indicator for the proportion of pregnant women with dental care in the municipality was 4% and in 2023 in the first four months it was 67% and in the second 71%. Of the population of health professionals involved with PNO, 37.5% participated in the study (n=18): community health agent, doctor, dentist, oral health assistant, nurse, nursing technician. The average age was 42.9 (±10.4) years, the majority were women (80%), not permanent employees (70%) and had been working in Primary Health Care for more than 10 years (50%). It was found that there is a defined flow for carrying out the PNO, with initial identification of pregnant women by the health agents and/or consultation with the nurse/doctor and referral for dental consultation. Collaborative work was essential for the PNO, with a division of responsibility for each professional. Reasons were given as to why PNO is important, as well as barriers such as myths, lack of knowledge among pregnant women and lack of training among professionals. The Previne Brasil Program was identified as a facilitator for increasing access and raising funds. The results suggest that the PNO is a complex issue, with many factors interfering, and that Previne Brasil is a facilitator for its operation. Based on these analyses, a protocol was proposed for improving the proportion of pregnant women with dental care.